2000
DOI: 10.1111/j.1751-3928.2000.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Magnetically Zoned Pluton, Tsushima, Japan

Abstract: : Systematic measurements of magnetic susceptibility were carried out at the outcrops of the Uchiyama granitic pluton, Tsushima Islands. The pluton consists of hornblende‐biotite granodiorite and biotite granite. It intrudes concordantly along an anticline axis of the Taishu Group in middle Miocene (16. 10. 5 Ma), and crops out in five areas. The results show that the low magnetic susceptibility facies (LM–facies, <100A‐10‐6 emu/g) always occurs in the peripheral part of the pluton, while the high magnetic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Among them, granitoids in Tsushima that are associated with vein-type Ag-Zn-Pb deposits are the representative examples in the inner zone of the Southwest Japan arc. The Tsushima granitoids exhibit magnetite-series character in their central portions whereas they are ilmenite-series (occasionally having accessory pyrrhotite) along the contact with the enclosing carbonaceous sedimentary formations (Shimada et al, 2000;Ishihara and Imai, 2000). The SO 3 contents of apatite in Tsushima granitic intrusions are quoted from Ishihara and Imai (2000).…”
Section: Southwest Japan-ryukyu Arc Kyushumentioning
confidence: 99%
“…Among them, granitoids in Tsushima that are associated with vein-type Ag-Zn-Pb deposits are the representative examples in the inner zone of the Southwest Japan arc. The Tsushima granitoids exhibit magnetite-series character in their central portions whereas they are ilmenite-series (occasionally having accessory pyrrhotite) along the contact with the enclosing carbonaceous sedimentary formations (Shimada et al, 2000;Ishihara and Imai, 2000). The SO 3 contents of apatite in Tsushima granitic intrusions are quoted from Ishihara and Imai (2000).…”
Section: Southwest Japan-ryukyu Arc Kyushumentioning
confidence: 99%
“…These values vary with chemical compositions, grain sizes and cooling rates (Dodson, 1973). Harrison et al (1985) have demonstrated that biotite has a strong compositional effect, with increasing Fe/Mg ratio corresponding to an increase in diffusivity of argon, but biotite grains from the pluton indicate uniform compositions with Fe/(Fe+Mg) ≈ 0.6 (Shimada et al, 2000). Although variation of Fe/(Fe+Mg) ratios can be widely seen within the amphibole samples (Fig.…”
Section: Uchiyama Plutonmentioning
confidence: 99%
“…The decrease in magnetic susceptibility of the Uchiyama pluton is considered to have occurred due to reduction by external volatiles from pelitic wall rocks of the Taishu Group (Shimada et al, 2000;Ishihara and H. IKEMI, N. SHIMADA and H. CHIBA 234 RESOURCE GEOLOGY : Imai, 2000). It means that the granitic body, which indicates low magnetic susceptibility, may have reacted well with the volatiles due to its slow cooling rate.…”
Section: Uchiyama Plutonmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrusions in the Taishu [4], Obira (granite porphyry) [5] and Chichibu mining districts were designated as granitic rocks related to Pb-Zn mineralization. We studied samples from the Ohkawame [6] and Daito-Yamasa [7] mining districts as granitic rocks related to Mo mineralization.…”
Section: Granitic Intrusions Investigatedmentioning
confidence: 99%